Quality of life of women as the criterion of effectiveness of premenstrual syndrome therapy - A V Ledina (IP Berlin A.V., 2013)
Quality of life is one of the criteria for therapy effectiveness assessment. The study's aim was to assess the indicators of quality of life of patients with premenstrual syndrome (PMS) of moderate and severe gravity before and after combined therapy via micro dosed contraceptives containing 20 mcg of ethinyl estradiol and 3 mg drospirenone in a 24/4 regimen. 122 patients aged 16-45 years were observed. To assess the quality of life and the impact of PMS on different aspects of life, patients in the late luteal phase of the menstrual cycle have filled twice - before and after treatment, a Medical Outcomes Study - Short Form (MOS-SF-36) questionnaire. After treatment a statistically significant reduction in the deformation parameters, both physical and psyhological components of health were shown.